2018
DOI: 10.1021/acs.jafc.8b04429
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Ferulate Esters as Multifunctional Food Additives: Antibacterial Activity and Mode of Action against Escherichia coli in Vitro

Abstract: This work aims to prepare ferulic acid alkyl esters (FAEs) through the lipase-catalyzed reaction between methyl ferulate and various fatty alcohols in deep eutectic solvents and ascertain their antibacterial activities and mechanisms. Screens of antibacterial effects of FAEs against Escherichia coli ATCC 25922 (E. coli) and Listeria monocytogenes ATCC 19115 (L. monocytogenes) revealed that hexyl ferulate (FAC6) exerted excellent bacteriostatic and bactericidal effects on E. coli and L. monocytogenes (minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 56 publications
2
44
1
Order By: Relevance
“…Lipophilicity is an important factor for exploring the mechanism of action of antimicrobial agent against pathogenic bacteria (Shi et al, 2018). Therefore, the theoretical partition coefficients (Clog P ) were considered for the current discussion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipophilicity is an important factor for exploring the mechanism of action of antimicrobial agent against pathogenic bacteria (Shi et al, 2018). Therefore, the theoretical partition coefficients (Clog P ) were considered for the current discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, low activity 5a−5e and 6a−6e had higher Clog P values (3.14–4.80). Shi et al have reported that ferulic acid and ferulic acid alkyl esters (FAC2) with 1.4212 and 2.1762 of Clog P values showed higher antibacterial activity against E. coli as compared with other similar compounds having higher Clog P values (Shi et al, 2018). Moreover, this similar trend also was reported by Wu et al They found auranofin analogs with lower log P values (1–2) exhibited better activity than some analogs with higher log P values (>3) against S. aureus, E. coli , and P. aeruginosa (Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, the protein and nucleic acid leakage in the PCA + HHP group was less than that of HHP group ( Figure 2 A,B), which contradicted with PI-based results, in which the PCA + HHP treatment led to greater membrane permeability. According to Shi et al [ 27 ], a slight increase in permeability may lead to K + and Mg 2+ leakage, but protein and nucleic acid leakage would require severe membrane damage (such as holes in the membranes, which were found in the AFM results). The K + and Mg 2+ leakage levels, of the PCA + HHP group, were higher than those of the HHP group ( Figure 2 C,D).…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration was determined by comparing and converting the absorbance with that of the standard protein solution (bovine serum albumin, 0.563 mg/mL). The intracellular nucleic acid content was determined at OD 260 nm using a UV-vis spectrophotometer in accordance with previous research [ 27 ] with modifications. The intracellular K + and Mg 2+ concentrations were determined using potassium [ 28 ] and magnesium assay kits [ 29 ], respectively, with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, alkyl ferulates synthesized by esterification of the ferulic acid with alcohols of 4–12 carbon atoms in a molecule catalyzed by lipase B from C. antarctica were the subject of studies by Shi et al ( 2018 , 2019 ). Among the obtained compounds, hexyl ferulate (Fig.…”
Section: Application Of Biocatalysis In the Synthesis Of Lipophilic Antioxidants And Antimicrobial Compoundsmentioning
confidence: 99%